Cache Valley virus as a cause of fetal abnormalities in a litter of three Boer kids. Issue 1 (8th March 2019) - Harvey, Jessica; Smith, Joseph; Jackson, Nicole; Kreuder, Amanda; Dohlman, Tyler; Smith, Jodi
Abstract : A 10‐month‐old Boer doe presented for dystocia. On caesarean section, three non‐viable fetuses, with multiple developmental abnormalities, including hydranencephaly were recovered. Subsequent testing demonstrated the presence of Cache Valley virus in the doe, kids and herdmates. Preventive efforts of insect control and delaying the breeding season to correspond to decreased insect activity resulted in no additional abnormalities in the herd over the two years after the presentation of this case.